Metaheuristics applied to vehicle routing. A case study. Part 2: genetic algorithm, compared to a heuristics solution - González Vargas, Guillermo; González Aristizábal, Felipe (Ingeniería e investigación, 2007)
This paper presents a solution to a vehicle-routing problem by using two different techniques. In the first instance, a genetic algorithm was applied (different experiments were done); later on the cluster first-route second methodology was used via heuristic sweep and local search, respectively. The results of the different techniques were then compared.